El mejor pastor descalzo, san Pascual Baylón o la incursión teatral de Ginés Campillo de Bayle. - VILLA, RAMÓN DOMÉNECH (Scripta, 2016)
During the last decades of the seventeenth century, which marked the end of the Royal House of Austria in Spain, a cleric born in Elche (Alicante), Ginés Campillo de Bayle, tried to participate in the literary world of the time. His life and work, for one reason or another, have always been linked to mystery, misfortune and low esteem. Valued cautiously by few, ignored or criticized by most, we have now in our hands, a part of his lyrical, narrative and theatrical productions. An example of a characteristic sugnere of Golden Century is, El mejor pastor descalzo, san Pascual Baylón, that our writer published during the last gasps of this symbolic period. The following article tries to be a brief analysis of that work, delving into its most signiicant features, and identifying what inluences and sources the author would used, without forgetting the literary peculiarities which beneited from the parish church of Santa Maria Mayor of his hometown.